2022
DOI: 10.1044/2022_aja-21-00233
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Use of Speech Testing in Adult Audiology

Abstract: Objective: The aim of this study was to evaluate hearing health care professionals' (HHPs) speech testing practices in routine adult audiology services and better understand the facilitators and barriers to speech testing provision. Design: A cross-sectional questionnaire study was conducted. Study Sample: A sample ( N = 306) of HHPs from the public (64%) and privat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…It is unclear whether audiologists are able to conduct cognitive tests sufficiently well and their utility in clinical situations needs evidencing ( 222 ). Speech testing might give some indication of overall ability and it has been suggested that it be more widely used ( 223 ) because standard audiometry provides no useful evidence regarding auditory processing and cognition. However, it is equally unlikely that a speech test score could equate directly to a specific hearing aid setting and user preference.…”
Section: Discussion: a Pragmatic Approach To Setting Hearing Aids For...mentioning
confidence: 99%
“…It is unclear whether audiologists are able to conduct cognitive tests sufficiently well and their utility in clinical situations needs evidencing ( 222 ). Speech testing might give some indication of overall ability and it has been suggested that it be more widely used ( 223 ) because standard audiometry provides no useful evidence regarding auditory processing and cognition. However, it is equally unlikely that a speech test score could equate directly to a specific hearing aid setting and user preference.…”
Section: Discussion: a Pragmatic Approach To Setting Hearing Aids For...mentioning
confidence: 99%
“…This would allow clearer insight of where and when these discussions happen, although may require additional training locally, and additional time to undertake this extra task. Alternative diagnostic testing, such as speech testing, could aid the clinical decision-making process [ 15 ] and explain regional variations in management.…”
Section: Discussionmentioning
confidence: 99%
“…Additional validation of these Chichewa questionnaires using a larger population would further confirm the consistency of the measures. Speech perception and speech in noise perception measures are used to guide and evaluate hearing aid fittings in audiology settings (Parmar et al, 2022), but Chichewa measures of this kind are not currently available. A Digits in Noise test, or similar, could be used in future for this purpose, if self-reported English-competence and age were considered (Potgieter et al, 2018).…”
Section: Discussionmentioning
confidence: 99%